The operationalisation of Corporate Social Responsibility (CSR) in a mining context - Isacowitz, Jenna Jade; Schmeidl, Susanne; Tabelin, Carlito (Resources policy, 2022)
Mining companies have publicly committed to improving sustainable development outcomes under the auspices of Corporate Social Responsibility (CSR), which is frequently framed as a ‘triple bottom line’ or balancing ‘profit’ with ‘people’ and ‘planet’. Despite the growing prominence of CSR, too little is known as to how mining companies translate this intended ‘triple bottom line’ into action. To this effect, eight in-depth interviews were conducted with representatives from Australia-based mining companies (defined as companies which hold major headquarters or operations within Australia); members of local communities affected by mining operations; and a subject matter expert (non-academic). Thematic analysis identified that as CSR is primarily driven by shareholder interests rather than company conviction, there is frequently a disconnect between company intentions and application of CSR. This study found that mining companies fail to clearly operationalise CSR (e.g., how success would look like) and how this is measured. This suggests that more needs to be done to move beyond paying lip service to CSR, and there is a need for standardised frameworks and metrics which can accurately evaluate the impact of CSR activities. This research argues that the integration of CSR into core business models and decision-making would ultimately build stakeholder trust and maintain a social license to operate (SLO). •There is frequently a disconnect between understanding and application of CSR.•Mining companies lack frameworks/assessment tools to measure the success of CSR.•Mining companies need solid contextual understanding to frame their CSR strategies.•CSR needs to be integrated in to operational strategies as core business practice.•Proactive and participatory stakeholder engagement enabled by clear accountability.